Work/Family Arrangements across the OECD: Incorporatingthe Female-Breadwinner Model - Kowalewska, H; Vitali, A (LIS Cross-National Data Center, 2019)
Studies of work/family arrangements over time and space typically analyse families by the extent to which they follow a ‘male-breadwinner’ versus a ‘dual-breadwinner’ model. Yet, this analytical framework overlooks an alternative set of labour-market arrangements that is becoming increasingly common across heterosexual couple-households in advanced economies, which is the ‘female-breadwinner’ model. Very little is known about these families, as studies typically assume that men in couple-households are full-time employed. To contribute to addressing this deficit in knowledge, we compare the economic characteristics of female-breadwinner couples with those of male-breadwinner families across 20 OECD countries through descriptive analyses using Luxembourg Income Study data. In so doing, we identify two ‘types’ of female breadwinners, which appear to be stratified by class. The first is the ‘pure’ female-breadwinner couple, in which the woman is in employment and the man is not. Pure female-breadwinner families are as poor as pure male-breadwinner households, if not poorer. What is more, as individuals, pure female breadwinners are typically low-educated and have significantly lower average earnings than pure male breadwinners. The second type is the ‘one-and-a-half’ female breadwinner model, in which the woman is in full-time employment and the man works part-time. One-and-a-half female breadwinners are generally doing better than pure female-breadwinners; yet, when we look at the individual labour earnings of one-and-a-half female breadwinners compared with their male counterparts, we find these women still earn far less. Without measures to address stubborn gender inequalities in earnings, the current policy imperative towards increasing women’s participation in (any) employment risks upholding masculine breadwinning norms and ideals. This in turn limits the abilities of families to respond to the complexity and unpredictability of modern life, when shock events or other circumstances (e.g. recession, illness) require a shift in breadwinning between partners.